Speed isn't everything: a multi-criteria analysis of broadband access speeds in the UK - Volker Stocker; Jason Whalley (International Telecommunications Society (ITS), 2016)
In this paper, we demonstrate that there is more to consumer experience than just broadband access speed. We identify and describe a complex and dynamic set of interactions that occur between different factors that collectively determine consumer experience. We suggest that the relationship between broadband speed and consumer experience follows an inverted U-shape. Access speed is necessary to provide consumers with a good experience, but it is not sufficient. Based on our findings, a more nuanced understanding of the market for broadband Internet access products is outlined and a foundation for deriving valuable policy implications is developed. The results are of particular relevance for the ongoing universal service discussions in the UK and other countries.
Keywords: 330; Internet Access; Broadband; QoS; QoE; Consumer Experience; Ofcom